Fire safety at shopping complex's food court / Muhammad Hafiz Mohd Noor and Edelin Hussien - Mohd Noor, Muhammad Hafiz; Hussien, Edelin (2020)
Fire accident in a food court at a shopping mall is getting more heard and serious all over the world. Fire safety is very important to manage and improve fire accidents from back again. Therefore, this research is conducted to analyse the causes of fire in, the knowledge of fire safety among the food court workers and to suggest the effective ways to improve fire safety in the food court at the shopping complex. In order to achieve the objectives of the research, the data and information are collected using primary and secondary data. The secondary data are written and published sources collected through books, articles, newspaper, websites and journals. The primary data for this research is using questionnaire in order to obtain a quantitative data. The data gathered through questionnaire is distributed to 100 respondents. The scope of this research only focuses on food court workers at the shopping complex. The respondents answered the questionnaire on a Likert's Scale and their answers are analysed using SPSS Version 25.0. For objective one (1) it was found that the respondents agreed that there are a lot of factors that can cause fire. For second (2) objectives, its was found that most of the food court workers know the fire safety equipment in the food court but not most of them know how to use that fire safety equipment in case of fire. For third (3) objectives, it is found that improvement on the various aspect of the fire safety is necessary to improve the efficiency of the fire safety equipment.